Fabric preparation method

SiO2 water-sol-based antibacterial agent was prepared by sol-gel method and combined with protease to modify the fiber surface, which solved the problem of insufficient antibacterial durability of existing antibacterial textiles, and achieved efficient, durable and low-toxic antibacterial effects.

CN119507203APending Publication Date: 2025-02-25WUJIANG FUHUA WEAVING
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411140646.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2021-10-29
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The antibacterial durability of existing antibacterial textiles is insufficient, and traditional antibacterial agents have problems such as high toxicity and easy to cause bacteria to develop resistance.

Method used

SiO2 water-sol-based antibacterial agent was prepared by sol-gel method. By combining chitosan and micron elemental silver composite antibacterial agent with alkyl siloxane, SiO2 water-sol-based antibacterial agent was formed, and the fiber surface was modified by protease. Carboxylic groups form dual effects of valence bonding and mechanical nail anchoring, improving the fixing strength of antibacterial agents.

Benefits of technology

It has achieved significant improvement in antibacterial effects and improved durability, reducing the toxicity and cost of antibacterial agents, and at the same time, the process is green and environmentally friendly, and the conditions are easy to control.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005001559170000121
    Figure BDA0005001559170000121
  • Figure BDA0005001559170000131
    Figure BDA0005001559170000131
  • Figure BDA0005001559170000132
    Figure BDA0005001559170000132
Patent Text Reader

Abstract

The invention discloses a fabric preparation method which comprises the following steps: modifying fibers of a fabric by using protease under an acidic condition, and keeping the pH value of a system in the modification process to be 3.0-4.0 all the time; and finishing the modified fabric by adopting polyalkyl siloxane hydrosol to obtain the fabric, the polyalkyl siloxane hydrosol is prepared by the following steps: adding a surfactant into a hydrochloric acid deionized water solution, stirring, after the surfactant is fully dissolved, adding a chitosan / micron elemental silver composite antibacterial agent, adding alkyl siloxane while stirring, and continuously stirring for reaction to obtain the polyalkyl siloxane hydrosol; the surface active agent is a mixture of sodium dodecyl benzene sulfonate and twin-80. According to the preparation method of the fabric, the prepared fabric is good in antibacterial property and durability.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is filed on October 29, 2021, with application number 2021112745265 and invention name “A SiO 2 A divisional application for the invention patent application for "Hydrosol-based antibacterial agent and its preparation method and application". Technical Field

[0002] The invention relates to the technical field of textiles, and in particular to a method for preparing a fabric. Background Art

[0003] Textiles, due to their loose and porous structure, are very easy to absorb excretions secreted by human metabolism, providing a favorable place and nutrients for the attachment and reproduction of microorganisms, and pathogenic bacteria multiply in large numbers. The presence of microorganisms on textiles not only affects their performance (such as mildew, catalysis, deterioration, etc.), but also poses a serious health threat to the user's health (such as causing skin diseases, inducing diseases when entering the body, etc.). For this reason, it is of great significance to protect human health to hinder and inhibit the metabolism and reproduction of microorganisms during the use and storage of fabrics through antibacterial finishing of textiles. In recent years, antibacterial textiles have become a research hotspot in the field of functional textiles.

[0004] Antibacterial textiles are usually made by adding antibacterial agents to textiles. There are two main preparation methods: the original fiber method and the post-finishing method. There are also methods of blending or interweaving to achieve antibacterial function. The post-finishing method refers to the use of coating or padding to attach antibacterial agents to the fiber surface to give the fabric an antibacterial effect. Because of its simple operation, it has become the most studied method for preparing antibacterial fabrics. However, the antibacterial durability of fabrics prepared by this method needs to be further improved. The post-finishing method refers to the method of loading antibacterial agents onto the surface of fabrics by physical, chemical or physical and chemical methods.

[0005] Antimicrobial agents refer to substances that can effectively inhibit the growth and reproduction of microorganisms or kill microorganisms. The quality of their performance directly determines the antimicrobial effect of textiles. According to the source, antimicrobial mechanism and composition structure, antimicrobial agents can be divided into inorganic antimicrobial agents, organic antimicrobial agents and natural antimicrobial agents. Inorganic antimicrobial agents are mainly divided into two categories: silver and copper. Although silver has a good antimicrobial effect, it is not only expensive, but also easily oxidized to form dark silver oxide or black elemental silver. Copper is cheap and has a certain antiviral effect, but its own color will cause the color of the fabric to change. Organic antimicrobial agents mainly include quaternary ammonium salts, guanidines, halogenated phenols and halamines. Although they have excellent antimicrobial properties, they are generally toxic and easily cause bacteria to develop drug resistance. Natural antimicrobial agents have become a class of antimicrobial agents with great development potential due to their good biocompatibility, natural degradability, and the fact that they will not cause bacteria to develop drug resistance. Chitosan is a product of chitin with some acetyl groups removed. It has an inhibitory effect on Escherichia coli and Staphylococcus aureus. Due to its abundant resources, it has become one of the most widely studied natural antibacterial agents. However, the antibacterial ability of chitosan is poor when used alone. Therefore, improving the antibacterial ability is the key to promoting the industrial application of chitosan.

[0006] At present, chitosan antimicrobial agents can be divided into two categories according to the preparation method: composite type and modified type. Composite chitosan antimicrobial agents have attracted much attention due to their simple preparation method and significant antimicrobial effect. However, composite chitosan antimicrobial agents still need to add adhesives or crosslinking agents during application to improve their binding force with fibers, which in turn affects the wearing performance of fabrics. According to literature reports, the most effective method to increase load strength is to allow fibers and antimicrobial agents to form valence bonds. Among them, the grafting method, which has been studied more, can form valence bonds between fibers and antimicrobial agents, but there are problems such as harsh process conditions and difficult to control uniformity.

[0007] The disclosure of the above background technology content is only used to assist in understanding the inventive concept and technical solution of the present invention. It does not necessarily belong to the prior art of this patent application. In the absence of clear evidence that the above content has been disclosed before the filing date of this patent application, the above background technology should not be used to evaluate the novelty and creativity of the present application. Summary of the invention

[0008] In view of this, in order to overcome the defects of the prior art, the object of the present invention is to provide a method for preparing a fabric with good antibacterial effect and good durability.

[0009] In order to achieve the above-mentioned purpose, in view of the shortcomings of the existing antibacterial protective fabrics, the present invention adopts a sol-gel method to prepare a safe, harmless or low-harmful high-efficiency composite antibacterial finishing agent that can form a valence bond with the fiber.

[0010] The present invention adopts the following technical solutions:

[0011] A SiO 2 The preparation method of the hydrosol-based antibacterial agent comprises the following steps:

[0012] The micron elemental silver dispersion and the chitosan solution are mixed, and the stirring is continued to obtain a chitosan / micron elemental silver composite antibacterial agent crude product after precipitation, and the chitosan / micron elemental silver composite antibacterial agent is obtained after washing and filtering;

[0013] Add surfactant and defoamer to deionized hydrochloric acid solution, stir, and add chitosan / micron silver composite antibacterial agent after the surfactant is fully dissolved, add alkyl siloxane while stirring, and continue to stir and react to obtain SiO 2 Hydrosol-based antimicrobial agent.

[0014] In some embodiments of the present invention, the hydrosol (SiO 2 The preparation method of the hydrosol-based antibacterial agent is as follows: adding a surfactant with a mass concentration of 0.1% and a defoamer with a mass concentration of 0.01% to a deionized hydrochloric acid solution with a mass concentration of 0.46%, stirring at a speed of 300r / min for 60min under the condition of a temperature of 25°C, and then adding a chitosan / micron elemental silver composite antibacterial agent with a mass ratio of 15% to alkylsiloxane after sodium dodecylbenzenesulfonate is fully dissolved, and stirring is continued for 60min to make the antibacterial agent uniformly dispersed, adding a 4% alkylsiloxane with a mass concentration of 4% within 5min under the stirring condition of 600r / min, and stirring is continued for 60min after the alkylsiloxane is added, and then heating to 60°C at a heating rate of 2°C / min, reacting for 30min under stirring to obtain SiO 2 Hydrosol-based chitosan / micron elemental silver composite antibacterial agent. The mass concentration in the present invention is the mass concentration of the corresponding substance in the formed solution, rather than the original concentration of the added substance.

[0015] According to some preferred embodiments of the present invention, the alkyl siloxane is preferably selected from one or more of methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, and γ-aminopropyltriethoxysilane.

[0016] According to some preferred implementation aspects of the present invention, the surfactant is a mixture of sodium dodecylbenzene sulfonate and twain-80 in a mass ratio of 1:0.1-0.3.

[0017] The principle of this step is: using a mixture of anionic sodium dodecylbenzene sulfonate and non-ionic TWAIN-80 as a surfactant, because the addition of TWAIN-80 will not change the charge of the hydrosol system, but can enhance the strength of the sodium dodecylbenzene sulfonate micelles, and at the same time can effectively reduce the viscosity of the hydrosol, thereby improving the stability of the hydrosol and the uniformity of the particle size; the addition of the defoamer can effectively prevent the surfactant from generating foam under high-speed stirring conditions, thereby avoiding affecting the dispersibility of the alkyl siloxane and affecting the final antibacterial effect.

[0018] According to some preferred embodiments of the present invention, in the preparation of the chitosan / micron elemental silver composite antibacterial agent, the mass of the added micron elemental silver is 5-10% of the mass of the chitosan.

[0019] According to some preferred implementation aspects of the present invention, the SiO 2 In the preparation of the hydrosol-based antibacterial agent, the mass of the added chitosan / micron elemental silver composite antibacterial agent is 10-20% of the mass of the added alkyl siloxane.

[0020] According to some preferred implementation aspects of the present invention, the chitosan solution is prepared by adding chitosan and acetic acid into deionized water to form a chitosan solution having a chitosan mass concentration of 2-5% and an acetic acid mass concentration of 1-2%.

[0021] According to some preferred implementation aspects of the present invention, the steps for preparing the micron elemental silver dispersion are as follows: sodium dodecylbenzene sulfonate and ethanol are added into deionized water, stirred, and after the sodium dodecylbenzene sulfonate is completely dissolved, 5 to 10% of the mass weight of the micron elemental silver to the chitosan is added while stirring.

[0022] According to some preferred implementation aspects of the present invention, the preparation of micron elemental silver comprises the following steps: adding polyvinyl pyrrolidone and a reducing agent to deionized water, wherein the mass concentration of polyvinyl pyrrolidone in the system is 0.5-1.0%, and the mass concentration of the reducing agent is 1-2%, stirring, and after the polyvinyl pyrrolidone and the reducing agent are completely dissolved, adjusting the pH of the reaction solution to 3-4 with a buffer solution, adding silver nitrate with a mass concentration of 2-5% under stirring, continuing to stir after adding, heating to 40-50°C, reacting at a constant temperature for 30-60 minutes, precipitating a crude micron elemental silver product, and obtaining micron elemental silver after washing and filtering.

[0023] In some embodiments of the present invention, the preparation of chitosan / micron elemental silver composite antibacterial agent comprises the following steps:

[0024] 1) Preparation of chitosan solution: Add chitosan with a mass concentration of 2-5% and acetic acid with a mass concentration of 1.0-2.0% into 200 mL of deionized water. The deacetylation degree of the chitosan used is ≥90%.

[0025] 2) Preparation of micron elemental silver dispersion: 0.1-0.2% sodium dodecylbenzene sulfonate and 2-5 mL ethanol are added to 50 mL deionized water, stirred at a speed of 300 r / min, and after the sodium dodecylbenzene sulfonate is completely dissolved, 5-10% micron elemental silver is added to the chitosan mass while stirring.

[0026] 3) Preparation of composite antibacterial agent: at 25-30°C, stir at a speed of 600r / min, slowly add the micron elemental silver dispersion into the chitosan solution within 10-20min, after the addition is complete, continue stirring for 120-240min, use a centrifuge to precipitate the crude chitosan / micron elemental silver composite antibacterial agent, then wash with deionized water for 3-5 times, and filter to obtain the chitosan / micron elemental silver composite antibacterial agent.

[0027] In some embodiments of the present invention, the preparation of micron elemental silver comprises the following steps: adding polyvinyl pyrrolidone with a mass concentration of 0.5-1.0% and a reducing agent with a mass concentration of 1-2% to 200 mL of deionized water at 25-30°C, stirring at a speed of 300 r / min, and after the polyvinyl pyrrolidone and the reducing agent are completely dissolved, adjusting the pH of the reaction solution to 3-4 with an acetic acid-sodium acetate buffer solution, slowly adding silver nitrate with a mass concentration of 2-5% within 5-10 minutes under stirring, continuing to stir for 10-20 minutes after the addition, and then heating to 40-50°C at a speed of 1-2°C / min, reacting at a constant temperature for 30-60 minutes, precipitating the micron elemental silver crude product with a centrifuge, and then washing with deionized water 3-5 times, and filtering to obtain micron elemental silver with a particle size of 1-20 μm.

[0028] According to some preferred embodiments of the present invention, the reducing agent used in the preparation process of the micron elemental silver is trisodium citrate, ascorbic acid, or a complex of the two.

[0029] The present invention also provides a SiO prepared according to the preparation method as described above. 2 Hydrosol-based antimicrobial agent.

[0030] The present invention also provides a SiO 2 Application of hydrosol-based antimicrobial agent in fabric preparation. In some embodiments of the present invention, the fabric preparation method comprises the following steps: surface modification of fabric fibers using protease under acidic conditions; then preparing polyalkylsiloxane hydrosol; finishing the modified fabric using the polyalkylsiloxane hydrosol to obtain the fabric; the surfactant used in the preparation of the polyalkylsiloxane hydrosol is a mixture of sodium dodecylbenzene sulfonate and twain-80. The fibers used in the fabric are aliphatic polyamide fibers.

[0031] According to some preferred embodiments of the present invention, the acidic condition has a pH value of 3.0-4.0, preferably 3.5.

[0032] According to some preferred embodiments of the present invention, a surfactant is used in the process of modifying the fibers of the fabric, wherein the surfactant is a nonionic surfactant, preferably a nonylphenol polyoxyethylene ether and aliphatic polyoxyethylene ether surfactants.

[0033] According to some preferred embodiments of the present invention, a buffer solution is used in the process of modifying the fibers of the fabric, and the buffer solution is composed of a mixture of 0.1-0.3 mol / L disodium hydrogen phosphate and 0.0.5-0.2 mol / L citric acid. Preferably, the buffer solution is composed of a mixture of 0.2 mol / L disodium hydrogen phosphate and 0.1 mol / L citric acid in a volume ratio of 3:7, so that the pH value of the system is maintained at about 3.5.

[0034] The principle of fiber surface modification is as follows: the fiber surface is modified by hydrolyzing the amide bond (-COONH-) to generate carboxyl groups (-COOH) that can react with the silanol (-Si-OH) on the surface of the silica hydrosol particles. At the same time, a microscopic rough structure is formed on the fiber surface through the stripping effect, and the durability of the finishing effect is improved through the dual effects of mechanical anchoring and valence bond combination; the optimal application pH value for acid protease to modify the polyamide fiber surface is about 3.5, and both acid and protease can hydrolyze the amide bond (-COONH-) in the molecular structure of polyamide fibers to generate A synergistic effect can be produced in the process of forming amino groups (-NH2) and carboxyl groups (-COOH); adjusting the pH with a buffer solution can effectively neutralize the carboxyl groups (-COOH) generated during the modification process, so that the pH value of the system is always maintained at around 3.5 to ensure the highest effectiveness of the protease; organic acids are more moderate in hydrolyzing amide bonds than inorganic strong acids, and the conditions are easy to control; adding non-ionic surfactants can improve the wettability of the fiber surface, accelerate fiber swelling, and thereby improve the spreading of the bio-enzyme treatment solution on the fiber surface, thereby increasing the modification efficiency by increasing the effective contact area between the bio-enzyme and the fiber surface.

[0035] According to some preferred embodiments of the present invention, the pH value of deionized water is adjusted to 3.0-4.0 with a buffer solution, and then a surfactant and a protease are added, wherein the amount of the surfactant is 1-1.5 times the critical micelle concentration (CMC), and the concentration of the protease in the system is 0.02-2.0 g / mL; the fabric is treated at a bath ratio of 1:10-35, and then the fabric is washed and dried.

[0036] The nonionic surfactant added in the process of protease modification of polyamide fiber can not only improve the wettability of fiber, but also improve the swelling performance of fiber, and increase the effective contact area between protease and fiber surface, so as to improve the treatment efficiency. Meanwhile, the main purpose of the present invention is to generate more carboxyl groups and form microscopic rough structure on the fiber surface through protease modification, and improve the fixing strength of the finishing agent on the fiber surface by combining the dual effects of valence bond binding and mechanical anchoring when the silica hydrosol-based antibacterial agent is used for finishing.

[0037] In some embodiments of the present invention, the specific steps of fiber surface modification are as follows: adjust the pH value of 1L deionized water to 3.5 with 20mL buffer solution, then add surfactant and 0.2-2.0g protease, the amount of surfactant is 1-1.5 times of CMC, treat the fabric at 40℃ for 2-6h, and the bath ratio is 1:30. After treatment, inactivate at 60℃ for 10min, take out the fabric, wash with water and dry.

[0038] According to some preferred implementation aspects of the present invention, the protease is papain, and the optimal application pH value of papain is 3.0-4.0. The acidity of this pH value will not have a significant effect on fiber damage, and can produce a synergistic effect with biological enzymes.

[0039] According to some preferred embodiments of the present invention, finishing the modified fabric comprises the following steps: adjusting the pH value of the polyalkylsiloxane hydrosol to 6-7 with an alkali agent, finishing the modified fabric by a padding method, and then washing and drying to produce the fabric.

[0040] According to some preferred embodiments of the present invention, the alkali agent refers to a sodium hydroxide solution with a mass concentration of 4-8 g / L.

[0041] In some embodiments of the present invention, the steps of polyalkylsiloxane finishing of modified fabrics are as follows: at 25-30°C, the pH value of the polyalkylsiloxane hydrosol is adjusted to 6-7 with an alkali agent, and the modified polyamide fabric is finished by a two-immersion and two-rolling method with a rolling rate of 60-100%, and then dried at a temperature of 80-90°C for 2-5 minutes, and then baked at a temperature of 140-160°C for 3-6 minutes, washed with water, and finally dried at a temperature of 80-100°C to make a multifunctional polyamide fabric.

[0042] The principle of this step is that polyamide fibers are easily hydrolyzed under acidic conditions, which in turn affects the performance of the fabric. Adjusting the pH value of the silica sol to 6-7 will neither cause rapid condensation of the sol particles nor significantly affect the fiber strength.

[0043] Due to the adoption of the above technical scheme, compared with the prior art, the present invention is beneficial in that: the preparation method of the fabric of the present invention generates more carboxyl groups on the fiber surface and forms a microscopic rough structure through protease modification, and when the silica hydrosol-based antibacterial agent is finished, the dual effects of valence bond bonding and mechanical anchoring are integrated to improve the fixing strength of the finishing agent on the fiber surface; the antibacterial agent combines the relevant characteristics of chitosan and micron elemental silver, further reduces the cost while ensuring the antibacterial property, and the preparation process is green and environmentally friendly, and the conditions are easy to control; the chitosan / micron elemental silver composite antibacterial agent is combined with alkyl siloxane to prepare SiO 2 A hydrosol-based antibacterial agent is applied to fabric preparation, and the prepared fabric has good antibacterial property and good durability. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0045] Figure 1 This is a microscopic magnified image of the original polyamide fiber used in the preferred embodiment of the present invention;

[0046] Figure 2 This is a microscopic enlarged picture of the polyamide fiber after bioenzyme modification in the preferred embodiment 1-1 of the present invention;

[0047] Figure 3 This is a comparison picture of the antibacterial effect of the fabrics prepared by the preferred embodiment 3-1 of the present invention and comparative examples 1-4 to 1-7. DETAILED DESCRIPTION

[0048] In order to enable those skilled in the art to better understand the technical solution of the present invention, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0049] Example 1-1 Fiber surface modification

[0050] Use 20mL buffer solution to adjust the pH value of 1L deionized water to 3.5, the optimal application value of protease, and then add 1.0g protease and 1.2CMC nonylphenol polyoxyethylene ether, and treat at 40℃ for 3h, with a bath ratio of 1:30. After treatment, inactivate at 60℃ for 10min, take out the fabric, wash it with water, and dry it.

[0051] Example 1-2 Fiber surface modification

[0052] Use 20mL buffer solution to adjust the pH value of 1L deionized water to 3.5, the optimal application value of protease, and then add 1.5g protease and 1.2CMC nonylphenol polyoxyethylene ether, and treat at 40℃ for 2h, with a bath ratio of 1:35. After treatment, inactivate at 60℃ for 10min, take out the fabric, wash it with water, and dry it.

[0053] Example 1-3 Fiber surface modification

[0054] Use 20mL buffer solution to adjust the pH value of 1L deionized water to 3.5, the optimal application value of protease, and then add 1.0g protease and 1.2CMC nonylphenol polyoxyethylene ether, and treat at 40℃ for 3h, with a bath ratio of 1:25. After treatment, inactivate at 60℃ for 10min, take out the fabric, wash it with water, and dry it.

[0055] Example 2-1 Preparation of hydrosol with antibacterial function

[0056] 1. Preparation of micron-sized elemental silver

[0057] At 25°C, add 0.7% polyvinyl pyrrolidone and 1% reducing agent to 200 mL deionized water, stir at 300 r / min, after the polyvinyl pyrrolidone and the reducing agent are completely dissolved, adjust the pH of the reaction solution to 3-4 with acetic acid-sodium acetate buffer solution, slowly add 3% silver nitrate within 8 minutes under stirring, continue stirring for 15 minutes after the addition, then heat to 40°C at a speed of 1.5°C / min, react at constant temperature for 50 minutes, precipitate elemental silver with a centrifuge, wash with deionized water 5 times, and obtain micron elemental silver by suction filtration.

[0058] 2. Preparation of chitosan / micronized silver composite antibacterial agent

[0059] Chitosan solution: chitosan with a mass concentration of 3% and acetic acid with a mass concentration of 1.0% were added to 200 mL of deionized water to dissolve.

[0060] Micron elemental silver dispersion: add 0.15% surfactant and 3mL ethanol into 50mL deionized water, stir at 300r / min, after sodium dodecylbenzene sulfonate is completely dissolved, add 6% micron elemental silver to the mass of chitosan while stirring.

[0061] At 25°C, stir at 600 r / min and slowly add the micron elemental silver dispersion into the chitosan solution within 10 min. After the addition is complete, continue stirring for 150 min. Use a centrifuge to precipitate the elemental silver, wash it with deionized water 5 times, and filter to obtain the chitosan / micron elemental silver composite antibacterial agent.

[0062] 3. SiO 2 Preparation of hydrosol-based antibacterial agent

[0063] A surfactant with a mass concentration of 0.1% and a defoamer with a mass concentration of 0.01% were added to a deionized hydrochloric acid solution with a mass concentration of 0.46%, and stirred at a speed of 300 r / min for 60 min at a temperature of 25°C. After sodium dodecylbenzene sulfonate was fully dissolved, a chitosan / micron elemental silver composite antibacterial agent with a mass ratio of 15% to alkylsiloxane was added, and stirring was continued for 60 min to make the antibacterial agent uniformly dispersed. Methyltrimethoxysilane with a mass concentration of 4% was added within 5 min under the stirring condition of 600 r / min. After the precursor was added, stirring was continued for 60 min, and then the temperature was raised to 60°C at a heating rate of 2°C / min, and the reaction was carried out for 30 min under stirring to obtain SiO 2 A hydrosol-based antibacterial agent, wherein the surfactant is a mixture of sodium dodecylbenzene sulfonate and Twain-80 in a mass ratio of 1:0.2.

[0064] Example 2-2 Preparation of hydrosol with antibacterial function

[0065] 1. Preparation of micron-sized elemental silver

[0066] At 25° C., add 0.5% polyvinyl pyrrolidone and 1.5% reducing agent to 200 mL deionized water, stir at 300 r / min, after the polyvinyl pyrrolidone and the reducing agent are completely dissolved, adjust the pH of the reaction solution to 3-4 with acetic acid-sodium acetate buffer solution, slowly add 5% silver nitrate within 8 minutes under stirring, continue stirring for 15 minutes after the addition, then heat to 40° C. at a speed of 1.5° C. / min, react at constant temperature for 30 minutes, precipitate elemental silver with a centrifuge, wash with deionized water 5 times, and obtain micron elemental silver by suction filtration.

[0067] 2. Preparation of chitosan / micronized silver composite antibacterial agent

[0068] Chitosan solution: chitosan with a mass concentration of 3% and acetic acid with a mass concentration of 1.0% were added to 200 mL of deionized water to dissolve.

[0069] Micron elemental silver dispersion: add 0.15% surfactant and 3mL ethanol into 50mL deionized water, stir at 300r / min, after sodium dodecylbenzene sulfonate is completely dissolved, add 10% micron elemental silver to the mass of chitosan while stirring.

[0070] At 25°C, stir at a speed of 600 r / min and slowly add the micron elemental silver dispersion into the chitosan solution within 10 minutes. After the addition is complete, continue stirring for 200 minutes, use a centrifuge to precipitate the elemental silver, wash it with deionized water for 5 times, and filter to obtain the chitosan / micron elemental silver composite antibacterial agent.

[0071] 3. SiO 2 Preparation of hydrosol-based antibacterial agent

[0072] A surfactant with a mass concentration of 0.16% and a defoamer with a mass concentration of 0.016% were added to a deionized hydrochloric acid solution with a mass concentration of 0.5%, and stirred at a speed of 300 r / min for 60 min at a temperature of 25°C. After sodium dodecylbenzene sulfonate was fully dissolved, a chitosan / micron elemental silver composite antibacterial agent with a mass ratio of 20% to alkylsiloxane was added, and stirring was continued for 90 min to make the antibacterial agent evenly dispersed. Propyltrimethoxysilane with a mass concentration of 4% was added within 5 min under the stirring condition of 600 r / min. After the precursor was added, stirring was continued for 60 min, and then the temperature was raised to 40°C at a heating rate of 1.5°C / min, and the reaction was carried out for 30 min under stirring to obtain SiO 2 A hydrosol-based antibacterial agent, wherein the surfactant is a mixture of sodium dodecylbenzene sulfonate and Twain-80 in a mass ratio of 1:0.3.

[0073] Example 2-3 Preparation of hydrosol with antibacterial function

[0074] 1. Preparation of micron-sized elemental silver

[0075] At 25° C., add 0.7% polyvinyl pyrrolidone and 1% reducing agent to 200 mL deionized water, stir at 300 r / min, after the polyvinyl pyrrolidone and the reducing agent are completely dissolved, adjust the pH of the reaction solution to 3-4 with acetic acid-sodium acetate buffer solution, slowly add 4% silver nitrate within 10 minutes under stirring, continue stirring for 15 minutes after the addition, then heat to 40° C. at a speed of 1.5° C. / min, react at constant temperature for 40 minutes, precipitate elemental silver with a centrifuge, wash with deionized water 5 times, and obtain micron elemental silver by suction filtration.

[0076] 2. Preparation of chitosan / micronized silver composite antibacterial agent

[0077] Chitosan solution: chitosan with a mass concentration of 3% and acetic acid with a mass concentration of 1.0% were added to 200 mL of deionized water to dissolve.

[0078] Micron elemental silver dispersion: add 0.1% surfactant and 3mL ethanol into 50mL deionized water, stir at 300r / min, after sodium dodecylbenzene sulfonate is completely dissolved, add 8% micron elemental silver to the mass of chitosan while stirring.

[0079] At 25°C, stir at 600 r / min and slowly add the micron elemental silver dispersion into the chitosan solution within 10 min. After the addition is complete, continue stirring for 150 min. Use a centrifuge to precipitate the elemental silver, wash it with deionized water 5 times, and filter to obtain the chitosan / micron elemental silver composite antibacterial agent.

[0080] 3. SiO 2 Preparation of hydrosol-based antibacterial agent

[0081] A surfactant with a mass concentration of 0.13% and a defoamer with a mass concentration of 0.013% were added to a deionized hydrochloric acid solution with a mass concentration of 0.46%, and stirred at a speed of 300 r / min for 60 min at a temperature of 25°C. After sodium dodecylbenzene sulfonate was fully dissolved, a chitosan / micron elemental silver composite antibacterial agent with a mass ratio of 20% to alkyl siloxane was added, and stirring was continued for 60 min to make the antibacterial agent uniformly dispersed. Under the stirring condition of 600 r / min, a mass concentration of 4% alkyl siloxane (the mass ratio of methyltrimethoxysilane to propyltrimethoxysilane was 3:1) was added within 5 min. After the precursor was added, stirring was continued for 60 min, and then the temperature was raised to 40°C at a heating rate of 2°C / min, and the reaction was carried out for 40 min under stirring to obtain SiO 2 A hydrosol-based antibacterial agent, wherein the surfactant is a mixture of sodium dodecylbenzene sulfonate and Twain-80 in a mass ratio of 1:0.1.

[0082] Examples 2-1 to 2-3 provide a method for preparing a multifunctional composite antibacterial finishing agent, which has the following advantages: simple process, stable and easy-to-control process parameters; the antibacterial finishing agent has excellent antibacterial effect; it has active groups that can form valence bonds with the fiber surface, and the antibacterial effect of the finished fabric is long-lasting; the finishing agent can simultaneously give the finished fabric good antibacterial and antibacterial properties, water repellency and soft feel.

[0083] Example 3-1 Preparation of fabric

[0084] The preparation method of the multifunctional fabric in this embodiment specifically includes the following steps:

[0085] (1) Fiber surface modification: The polyamide fabric is modified by the fiber surface modification method in Example 1-1;

[0086] (2) Preparation of composite antibacterial finishing agent: SiO 2 Hydrosol-based chitosan / micron elemental silver composite antibacterial agent.

[0087] (3) Finishing of modified fabric with polyalkylsiloxane: At 25°C, the pH value of the polyalkylsiloxane hydrosol-based antibacterial agent in step (2) is adjusted to 6-7 with an alkali agent, and the modified polyamide fabric in step (1) is finished by a double dipping and double rolling method with a rolling rate of 80%, followed by drying at 80°C for 2 min, and then baking at 140°C for 3 min, washing with water, and finally drying at 80°C to produce a multifunctional polyamide fabric.

[0088] Example 3-2 Preparation of fabric

[0089] The preparation method of the multifunctional fabric in this embodiment specifically includes the following steps:

[0090] (1) Fiber surface modification: The polyamide fabric is modified using the fiber surface modification method in Example 1-2;

[0091] (2) Preparation of composite antibacterial finishing agent: SiO 2 Hydrosol-based chitosan / micron elemental silver composite antibacterial agent.

[0092] (3) Finishing of modified fabric with polyalkylsiloxane: At 25°C, the pH value of the polyalkylsiloxane hydrosol-based antibacterial agent in step (2) is adjusted to 6-7 with an alkali agent, and the modified polyamide fabric in step (1) is finished by a double dipping and double rolling method with a rolling rate of 80%, followed by drying at 80°C for 2 min, and then baking at 140°C for 3 min, washing with water, and finally drying at 80°C to produce a multifunctional polyamide fabric.

[0093] Example 3-3 Preparation of fabric

[0094] The preparation method of the multifunctional fabric in this embodiment specifically includes the following steps:

[0095] (1) Fiber surface modification: The polyamide fabric is modified by the fiber surface modification method in Examples 1-3;

[0096] (2) Preparation of composite antibacterial finishing agent: SiO 2 Hydrosol-based chitosan / micron elemental silver composite antibacterial agent.

[0097] (3) Finishing of modified fabric with polyalkylsiloxane: At 25°C, the pH value of the polyalkylsiloxane hydrosol-based antibacterial agent in step (2) is adjusted to 6-7 with an alkali agent, and the modified polyamide fabric in step (1) is finished by a double dipping and double rolling method with a rolling rate of 80%, followed by drying at 80°C for 2 min, and then baking at 140°C for 3 min, washing with water, and finally drying at 80°C to produce a multifunctional polyamide fabric.

[0098] Examples 3-1 to 3-3 provide a method for preparing a multifunctional polyamide fabric, which has the following advantages: the process is simple, and the process parameters are stable and easy to control; the fabric has excellent hydrophobicity, antistatic properties and a comfortable feel; the fabric has long-lasting antibacterial properties and good washability.

[0099] Comparative Example 1-1

[0100] The difference between this comparative example and Example 1-1 is that in the fiber surface modification method of this comparative example, when protease is used for modification, no nonionic surfactant is added. The remaining steps of this comparative example are basically the same as those of Example 1-1.

[0101] Comparative Example 1-2

[0102] The difference between this comparative example and Example 1-1 is that the pH value of the control system in the fiber surface modification method of this comparative example is 4.2. The remaining steps of this comparative example are basically the same as those of Example 1-1.

[0103] Comparative Examples 1-3

[0104] The difference between this comparative example and Example 1-1 is that the pH value of the control system in the fiber surface modification method of this comparative example is 2.8. The remaining steps of this comparative example are basically the same as those of Example 1-1.

[0105] Comparative Examples 1-4

[0106] The difference between this comparative example and Example 3-1 is that in this comparative example, SiO 2 When the hydrosol-based antibacterial agent is used, micron elemental silver is used to replace the chitosan / micron elemental silver composite antibacterial agent, and the remaining steps of this comparative example are basically the same as those of Example 2-1 and Example 3-1.

[0107] Comparative Examples 1-5

[0108] The difference between this comparative example and Example 3-1 is that in this comparative example, SiO 2 When the hydrosol-based antibacterial agent is used, nano-elemental silver is used to replace the chitosan / micron elemental silver composite antibacterial agent, and the remaining steps of this comparative example are basically the same as those of Example 2-1 and Example 3-1.

[0109] Comparative Examples 1-6

[0110] The difference between this comparative example and Example 3-1 is that in this comparative example, SiO 2 When the hydrosol-based antibacterial agent is used, chitosan is used to replace the chitosan / micron elemental silver composite antibacterial agent, and the remaining steps of this comparative example are basically the same as those of Example 2-1 and Example 3-1.

[0111] Comparative Examples 1-7

[0112] The difference between this comparative example and Example 3-1 is that in this comparative example, SiO 2 When the hydrosol-based antibacterial agent is used, chitosan / nano elemental silver composite antibacterial agent is used to replace chitosan / micron elemental silver composite antibacterial agent, and the remaining steps of this comparative example are basically the same as those of Example 2-1 and Example 3-1. Among them, nano elemental silver is prepared by a conventional method, and then chitosan / nano elemental silver composite antibacterial agent is prepared by step 2 in Example 2-1.

[0113] Comparative Examples 1-8

[0114] The difference between this comparative example and Example 3-1 is that the fabric preparation method of this comparative example does not include step (1) in Example 3-1, that is, this comparative example does not perform surface modification treatment on the fiber. The remaining steps of this comparative example are basically the same as those of Example 3-1.

[0115] Results and Discussion

[0116] (1) Fiber surface modification effect test

[0117] The fiber modified fabrics prepared in Examples 1-1 to 1-3 and Comparative Examples 1-1 to 1-3 were tested for the terminal carboxyl content and weight loss rate as follows. The terminal carboxyl content was tested by the method described on page 13 of the patent specification of Application No. 200580018511.5, entitled Method for Modifying Polyamide; the weight loss rate was tested by a constant temperature dry weight method, specifically, the fabric was dried in an oven at 105-110°C until constant weight balance (about 4 hours), and the weight was measured using an analytical balance, weight loss rate = (W 0 -W 1 ) / W 0 ×100%, where: W 0 W is the weight of fabric before treatment; 1 is the weight of the fabric after treatment. The test results of the modification effect are shown in Table 1 below:

[0118] Table 1 Test results of fiber surface modification effect

[0119]

[0120]

[0121] The test results in Table 1 show that the terminal carboxyl content of the fiber treated in the example is significantly higher than that of the fiber treated in the comparative example. The terminal carboxyl content of the fiber treated in Example 1-1 is higher than that of the fiber treated in the comparative example 1-1, indicating that the addition of the nonionic surfactant increases the hydrolysis rate of the amide bond. The terminal carboxyl content of the fiber treated in Example 1-2 is the highest because the mass concentration of the protease in Example 1-2 is high, and there are more effective contact opportunities between the fiber and the biological enzyme per unit time.

[0122] The terminal carboxyl content of the fiber treated in Comparative Example 1-1 is higher than that of the fiber treated in Comparative Example 1-2 and Comparative Example 1-3. This may be because the pH value of the treatment solution of Comparative Example 1-1 is within the optimal active pH range of papain, so the terminal carboxyl content of the fiber treated in Comparative Example 1-1 is the highest among the fibers treated in the comparative examples. In addition, compared with Comparative Example 1-2 and Comparative Example 1-3, the terminal carboxyl content of the fiber treated in Comparative Example 1-3 is slightly higher. This may be because the pH value of the treatment solution of Comparative Example 1-3 is relatively low (pH=2.8). The stronger the acidity, the worse the stability of the amide bond. The weight loss rate of the fiber treated in the comparative example shows that the weight loss of the fiber is caused by the combined action of acidity and protease. The terminal carboxyl content of the fiber treated in Comparative Example 1-1 is the largest, but the weight loss rate is not the largest, indicating that the hydrolysis of the amide bond by the protease is more moderate than the hydrolysis of the amide bond by the acidic condition, so that the polyamide molecular chain will not be broken in a short time to generate small molecules and separate from the fiber body.

[0123] (2) Antibacterial rate test

[0124] like Figure 3 As shown, the fabrics prepared in Examples 3-1 to 3-3 and Comparative Examples 1-4 to 1-7 were tested for antibacterial rate; the test method for antibacterial rate was based on GB / T 20944.1-2007 Evaluation of antibacterial properties of textiles Part 1: Agar plate diffusion method. The test results of antibacterial rate are shown in Table 2 below:

[0125] Table 2 Antibacterial rate test results

[0126]

[0127]

[0128] The test results in Table 2 show that when alkyl polysiloxane hydrosol is used as the matrix, the antibacterial property of chitosan is the worst (Comparative Examples 1-6), the antibacterial property of micron elemental silver (Comparative Examples 1-4) and the antibacterial property of nano elemental silver (Comparative Examples 1-5) both reach 100%, and elemental silver can significantly improve the antibacterial property of chitosan. The antibacterial property of chitosan / micron elemental silver (Example 3-1, Example 3-2 and Example 3-3) is similar to that of elemental silver (Comparative Examples 1-4 and Comparative Examples 1-5), and is better than the antibacterial property of chitosan / nano elemental silver (Comparative Example 1-7). Cause analysis: Chitosan is a porous material. When elemental silver is compounded with chitosan, part of the elemental silver is adsorbed on the surface of chitosan, and the other part is adsorbed into the pores of chitosan. The smaller the particle size of elemental silver, the greater the probability of adsorption into the pores of chitosan. Elemental silver is a contact antibacterial agent, so the antibacterial property of chitosan / micron elemental silver (Example) is better than that of chitosan / nano elemental silver (Comparative Examples 1-7).

[0129] (3) Durability test

[0130] The fabrics prepared in Examples 3-1 to 3-3 and Comparative Examples 1-8 were tested for antibacterial rate, hand feel and static contact angle as follows, wherein the test method for antibacterial rate refers to GB / T 20944.1-2007 Evaluation of antibacterial properties of textiles Part 1: Agar plate diffusion method; the hand feel test adopts the hand touch method; the static contact angle test adopts OCA50Micro fully automatic single fiber contact angle measuring instrument (German Dataphysics Instrument Co., Ltd.); the washing method refers to GB / T 8629-2017 Household washing and drying procedures for textile testing. The test results are shown in Table 3 below:

[0131] Table 3 Test results

[0132]

[0133]

[0134] The test results in Table 3 show that when the polyamide fabric is finished with a polyalkylsiloxane hydrosol-based antibacterial agent, the antibacterial property, feel and static contact angle of the fabric prepared in Comparative Examples 1-8 (without bioenzyme modification) are similar to those of the fabric prepared in Example 3-1 (bioenzyme modified), but after 20 or 50 washes, the various properties of the fabric prepared in Example 3-1 are significantly better than those of the fabric prepared in Comparative Examples 1-8. The main reason is that bioenzyme modification can not only form carboxyl groups (-COOH) on the fiber surface that are valence-bonded with silanol groups (Si-OH), but also form a microscopic rough structure. The rough structure produces a mechanical meshing effect with the polyalkylsiloxane coating, thereby improving the durability of the finishing effect.

[0135] Table 3 also shows that changing the polyalkylsiloxane precursor (i.e., the specific substance of alkylsiloxane) can give the finished fabric a different feel (Example 3-1, Example 3-2, and Example 3-3), but will not affect the antibacterial property (i.e., antibacterial rate) and hydrophobicity (i.e., static contact angle), nor will it have a significant effect on the durability of the finishing effect.

[0136] In the preparation method of the present invention, when modifying the fiber, the pH of the system is controlled to be about 3.5. The acidity at this time has a synergistic effect with the stripping of the polyamide fiber surface by the protease. The stripped fiber can not only effectively increase its adsorption amount of the polyalkylsiloxane hydrosol, but also improve the durability of the effect through mechanical anchoring and valence bond bonding (-COOH on the fiber and -OH on the polyalkylsiloxane). At the same time, the film formed by the polyalkylsiloxane can compensate for the damage caused by the stripping effect.

[0137] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a fabric, characterized in that: The steps include: The fibers of the fabric are modified by using protease under acidic conditions, and the pH value of the system is kept at 3.0-4.0 during the modification process; The modified fabric is finished by using polyalkylsiloxane hydrosol to obtain the fabric; The polyalkylsiloxane hydrosol is prepared by the following steps: Adding a surfactant to a deionized hydrochloric acid solution, stirring, and after the surfactant is fully dissolved, adding a chitosan / micron elemental silver composite antibacterial agent, adding an alkyl siloxane while stirring, and continuing to stir the reaction to obtain a polyalkyl siloxane hydrosol; The surfactant is a mixture of sodium dodecylbenzene sulfonate and Twain-80.

2. The preparation method according to claim 1, characterized in that: The surfactant is a mixture of sodium dodecylbenzene sulfonate and Twain-80 in a mass ratio of 1:0.1-0.

3.

3. The preparation method according to claim 1, characterized in that: The acidic condition has a pH value of 3.0-4.

0.

4. The preparation method according to claim 1, characterized in that: A buffer solution is used in the process of modifying the fibers of the fabric, wherein the buffer solution is a mixture of 0.1-0.3 mol / L disodium hydrogen phosphate and 0.0.5-0.2 mol / L citric acid.

5. The preparation method according to claim 1, characterized in that: A surfactant is used in the process of modifying the fibers of the fabric, and the amount of the surfactant used is 1-1.5 times the critical micelle concentration.

6. The preparation method according to claim 5, characterized in that: The surfactant used in fiber modification is a nonylphenol polyoxyethylene ether or aliphatic polyoxyethylene ether surfactant.

7. The preparation method according to claim 1, characterized in that: The modification steps are: adjusting the pH value of deionized water to 3.0-4.0 with a buffer solution, adding protease, treating the fabric under the condition of a bath ratio of 1:25-35, and then washing and drying the fabric.

8. The preparation method according to claim 1 or 7, characterized in that: During the modification, the concentration of the protease in the system is 0.02-2.0 g / mL.

9. The preparation method according to claim 1 or 7, characterized in that: The protease is papain.

10. The preparation method according to claim 1, characterized in that: Finishing the modified fabric includes the following steps: adjusting the pH value of the polyalkylsiloxane hydrosol to 6-7 with an alkali agent, finishing the modified fabric with a padding method, and then washing and drying to prepare the fabric.

11. The preparation method according to claim 10, characterized in that: The alkali agent refers to a sodium hydroxide solution with a mass concentration of 4-8g / L.

12. The preparation method according to claim 1, characterized in that: The fibers of the fabric are aliphatic polyamide fibers.

13. The preparation method according to claim 1, characterized in that: In the chitosan / micron elemental silver composite antibacterial agent, the mass of the micron elemental silver is 5-10% of the mass of the chitosan.

14. The preparation method according to claim 1, characterized in that: In the preparation of the polyalkylsiloxane hydrosol, the mass of the added chitosan / micron elemental silver composite antibacterial agent is 10-20% of the mass of the added alkylsiloxane.

15. The preparation method according to claim 1, characterized in that: The chitosan / micron elemental silver composite antibacterial agent is prepared by the following steps: mixing a micron elemental silver dispersion and a chitosan solution, stirring, and precipitating to obtain a chitosan / micron elemental silver composite antibacterial agent crude product, and washing and filtering to obtain the chitosan / micron elemental silver composite antibacterial agent.

16. The preparation method according to claim 15, characterized in that: The preparation steps of the chitosan solution are as follows: chitosan and acetic acid are added into deionized water, and the mass concentration of chitosan in the formed chitosan solution is 2-5%, and the mass concentration of acetic acid is 1-2%.

17. The preparation method according to claim 15, characterized in that: The preparation steps of the micron elemental silver dispersion are as follows: sodium dodecylbenzene sulfonate and ethanol are added into deionized water, stirred, and after the sodium dodecylbenzene sulfonate is completely dissolved, 5-10% of the micron elemental silver is added into the water while stirring.

18. The preparation method according to claim 17, characterized in that: The preparation of the micron elemental silver comprises the following steps: adding polyvinyl pyrrolidone and a reducing agent into deionized water, stirring, adjusting the pH value of the reaction solution to 3-4 with a buffer solution after the polyvinyl pyrrolidone and the reducing agent are completely dissolved, adding silver nitrate with a mass concentration of 2-5% under stirring, continuing to stir after the addition, heating to 40-50° C., reacting at a constant temperature for 30-60 minutes, precipitating a micron elemental silver crude product, and obtaining the micron elemental silver after washing and filtering.

19. The preparation method according to claim 18, characterized in that: Polyvinyl pyrrolidone and a reducing agent are added into deionized water, wherein the mass concentration of polyvinyl pyrrolidone in the system is 0.5-1.0%, and the mass concentration of the reducing agent is 1-2%.

20. The preparation method according to claim 18, characterized in that: The reducing agent used in the preparation process of the micron elemental silver is one or both of trisodium citrate and ascorbic acid.

Citation Information

Patent Citations

  • Method for modifying polyamide

    CN1965124A